2008
DOI: 10.3200/jach.57.3.309-314
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Factors in Collegiate Eating Disorder Pathology: When Family Culture Clashes With Individual Culture

Abstract: Abstract. Objective: The authors evaluated the validity of familial enmeshment (extreme proximity in family relationships) as a risk factor for eating disorders across cultural value orientations. They tested the hypothesis that although familial enmeshment may be a risk factor for eating disorder pathology for (1) participants of non-Asian descent or (2) culturally independent participants, enmeshment will not be a risk factor for (1) participants of Asian descent or (2) culturally interdependent participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Our findings regarding the differential associations between dimensions of academic motivation and indices of suicidal risk suggest the value in assessing for academic motivation using all six intrinsic and extrinsic dimensions to best identify which motivational dimensions to facilitate or discourage. For example, given that extrinsic introjected regulation was found to predict both depressive symptoms and suicidal behaviors, it may be important for college counselors to assist students in effectively managing different, and sometimes competing, motives (e.g., internal vs. external motives; Tomiyama & Mann, ) to decrease potential suicidal risk. Indeed, consistent with the finding that nearly 75% of incoming college students have indicated that they were attending college to get a better job or to make more money (Pryor, Hurtado, Sharkness, & Kom, ) and that vocational decision‐making processes have been found to be associated with experiences of anxiety in college students (Hawkins, Bradley, & White, ), our findings suggest that college counselors should be aware that an overemphasis on vocational outcomes of higher education (e.g., economic and job security) may be harmful to college students’ well‐being (Pisarik, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings regarding the differential associations between dimensions of academic motivation and indices of suicidal risk suggest the value in assessing for academic motivation using all six intrinsic and extrinsic dimensions to best identify which motivational dimensions to facilitate or discourage. For example, given that extrinsic introjected regulation was found to predict both depressive symptoms and suicidal behaviors, it may be important for college counselors to assist students in effectively managing different, and sometimes competing, motives (e.g., internal vs. external motives; Tomiyama & Mann, ) to decrease potential suicidal risk. Indeed, consistent with the finding that nearly 75% of incoming college students have indicated that they were attending college to get a better job or to make more money (Pryor, Hurtado, Sharkness, & Kom, ) and that vocational decision‐making processes have been found to be associated with experiences of anxiety in college students (Hawkins, Bradley, & White, ), our findings suggest that college counselors should be aware that an overemphasis on vocational outcomes of higher education (e.g., economic and job security) may be harmful to college students’ well‐being (Pisarik, ).…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate diagnosis and treatment of ED is critical to reduce burden of illness and mortality 47, 48 and to promote mental health and wellness and enhance students’ academic success. Clearly, such programs should be adapted and culturally tailored to meet the needs of both female and male students from various racial and ethnic backgrounds 46, 49…”
Section: Commentmentioning
confidence: 99%
“…Familial relationships which lack cohesion can range from enmeshment signalling interactions which lack boundaries, to low family connectedness. Tomiyama and Mann [ 41 ] found Asian-Americans were the only ethnic group to have a non-significant relationship between familial enmeshment and ED pathology. Similarly, Han [ 30 ] found no significant association between insecure parental attachment and restricted eating.…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunctional familial cohesion is known to influence the development and maintenance of eating pathology, as families of ED patients have been commonly characterised as having high enmeshment and a lack of familial cohesion [ 56 , 57 ]. However, the findings of this review have exhibited an opposing view [ 30 , 41 ], where familial enmeshment and insecure parental attachment has not been pathological for Asian youth. Kirschner [ 58 ] found familial enmeshment may be more culturally normative in collectivist Asian cultures, than for independence-oriented Western cultures where such interactions can increase psychological stress.…”
Section: Discussionmentioning
confidence: 99%